2004
DOI: 10.1016/j.jacc.2004.06.057
|View full text |Cite
|
Sign up to set email alerts
|

Identification of less-irradiating tube angulations in invasive cardiology

Abstract: The PA views and RAO views >or=40 degrees , heretofore unconventional in clinical routine, should be favored over steep LAO projections >or=40 degrees whenever possible. Tube angulations that are radiation intensive to the patient exponentially increase the operator's radiation risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
98
0
14

Year Published

2005
2005
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(122 citation statements)
references
References 28 publications
9
98
0
14
Order By: Relevance
“…The sagittal angulations of the X-ray beam were not taken into account in this figure. The lateral projection (LAO90) is the most frequent projection leading to the MSD, in agreement with Kuon et al [17].…”
Section: Maximum Skin Dosesupporting
confidence: 90%
“…The sagittal angulations of the X-ray beam were not taken into account in this figure. The lateral projection (LAO90) is the most frequent projection leading to the MSD, in agreement with Kuon et al [17].…”
Section: Maximum Skin Dosesupporting
confidence: 90%
“…In our study, the contribution of radiation doses to the overall KAP from LAO45°‐CAU35° and PA‐CAU40° were 16% and 11%, respectively, due to high tube potential of 120 kV and tube current of 21.4 mA compared to other angiographic projections (Table 2). Kuon et al (16) reports that LAO45°‐CAU35° involves a 2.6 fold increase in KAP/sec and 7.6 fold increase in operator doses compared to PA‐CAU30°. However these measurements were extensively carried out using an anthropomorphic RANDO phantom.…”
Section: Discussionmentioning
confidence: 99%
“…There is an increased number of interventions performed annually, (15) and contribution of radiation doses from individual projections is not widely reported in clinical setup to the extent of providing awareness among interventionalists as the study protocols may vary. However, there are studies in literature on radiation doses from various projections on anthropomorphic phantoms (16) . Hence it is necessary to monitor radiation doses and their associated risks during cardiovascular interventions.…”
Section: Introductionmentioning
confidence: 99%
“…This evaluation was largely based on deriving clinical information and did not balance the clinical information yield with the radiation consequence of the selection of projections. Papers such as the one by Kuon et al [13] have shown that significant dose reduction can be achieved in situations where multiple view options exist by selecting the view with the lowest per unit exposure.…”
mentioning
confidence: 99%